2016
DOI: 10.1016/j.toxicon.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The toxic effects of microcystin-LR on mouse lungs and alveolar type II epithelial cells

Abstract: Objectives Microcystin-leucine arginine (MC-LR) is produced by cyanobacteria and can accumulate in lungs through blood circulation. However, the effect of MC-LR on lung remains unclear. In this study, we investigated the chronic, low-dose effect of MC-LR on mouse lung tissues and the influence of MC-LR on mouse alveolar type II epithelial cells (ATII cells). Methods MC-LR was orally administered to mice at 0, 1, 10, and 40 μg/L for 6 consecutive months and mouse lungs were obtained for histopathological and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The chronic low-dose of MC-LR exposure resulted to alveolar collapse, lung cell apoptosis and breach of cell junction integrity. ATII cells were also capable to uptake MC-LR and induced apoptosis and disrupted cell junction integrity [52]. Chronic oral administration of MC-LR also resulted in mitochondrial DNA (mtDNA) neuron damage and histopathological abnormalities as well as mtDNA damage were evident in the hippocampus and cerebral cortex with distinct effects on these two brain regions [53].…”
Section: Toxicity and Carcinogenicitymentioning
confidence: 99%
“…The chronic low-dose of MC-LR exposure resulted to alveolar collapse, lung cell apoptosis and breach of cell junction integrity. ATII cells were also capable to uptake MC-LR and induced apoptosis and disrupted cell junction integrity [52]. Chronic oral administration of MC-LR also resulted in mitochondrial DNA (mtDNA) neuron damage and histopathological abnormalities as well as mtDNA damage were evident in the hippocampus and cerebral cortex with distinct effects on these two brain regions [53].…”
Section: Toxicity and Carcinogenicitymentioning
confidence: 99%
“…MC-LR-induced hepatotoxicity occurs by inhibiting protein phosphatase 1 and 2A (PP1 and PP2A) and inducing the production of ROS, followed by the destroying the cell cytoskeleton, eventually leads to liver cells necrosis and apoptosis [10,12]. In addition to the damage to the liver, some studies revealed that MCs also can cause harm to the intestines, brain, gonad, lung, and heart [13][14][15][16][17]. Recently, MCs have been reported to have penetrated renal cells in an OATPs dependent manner, subsequently promoting the accumulation of MC-LR [11,18].…”
Section: Introductionmentioning
confidence: 99%
“…The results of our study are mostly consistent with findings of Wang et al [25], who found no significant effect of 10 µM MC-LR on viability in A549 human non-small lung cancer cells following 24-h exposure. On the contrary, Li et al [29] found that 10 µM MC-LR significantly reduced (EC50) cell survival in HBE cells after 24 h, and concentrations ≥50 nM were cytotoxic to immortalized murine alveolar type II cell line [45]. To compare with other epithelial cell lines, a decreased viability of rat Sertoli cells was found after 24-h exposure to 8-32 µM MC-LR [61].…”
Section: Discussionmentioning
confidence: 99%
“…However, the toxicological tipping point of the adaptive stress response may be surpassed with further cyanotoxin concentration increase and adverse effects on bronchial epithelial layers might be expected, as shown for CYN [67]. In addition, MC-LR-induced reduction of viability in murine epithelial alveolar type II (ATII) cells was accompanied by a dose-dependent decrease of TEER values and reduced expression of tight junction proteins (e.g., ZO-1, occludin) [45]. MC-LR also decreased the expression of tight junction proteins in murine Sertoli cells [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation